Optimization of Lung Vital Capacity to Improve Athlete Fitness - Munadi Munadi; Rachmad Suhanda; Zulkarnain Zulkarnain; Mulkan Azhari; Winda Yulia (Journal of Social Research, 2024)
Physical training and fitness are important aspects in an athlete's readiness to achieve optimal performance in their sport. One important indicator of fitness is vital lung capacity, which measures the maximum amount of air that can be moved into and out of the lungs. The aim of this study was to investigate the optimization of vital lung capacity as a strategy to improve athlete fitness. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that optimizing lung capacity to improve athlete fitness can be done through several methods, including breathing exercises, physical training and aerobic training. Increasing vital lung capacity can also help minimize the risk of injury, as a stronger respiratory system is able to prevent excessive fatigue. Overall, this can have a positive impact on athletes' achievements, both at national, regional and international levels, as well as representing the country, region or institution they are fighting for.